The essentials of supply chain management : new business concepts and applications - Min, Hokey, 1954- ([New York, NY] : Pearson Education LTD, 2015)
"Focusing on outcomes throughout, The Essentials of Supply Chain Management shows how to achieve continuous organizational success by applying modern supply chain concepts. Reflecting his extensive recent experience working with leading executives and managers, Min teaches highly-effective methods for supply chain thinking and problem-solving. You'll master an integrated Total System Approach that places functions like inventory control and transportation squarely in context, helping you smoothly integrate internal and external functions, and establish effective inter-firm cooperation and strategic alliances across complex supply chains."--provided from Amazon.com.
Includes bibliographical references and index.
Keywords: Business logistics; Supply Chain Management